Edukasi Tehnik SADARI dan SADARNIS sebagai Upaya Deteksi Dini Kanker Payudara - Fadillah None None (Universitas Muhammadiyah Palembang, 2025)
Breast cancer is one of the leading cause of cancer related death among women in Indonesia. Breast self examination (BSE) and clinical breast examination (CBE) have been proven effective in reducing diagnostic delays. However, public knowledge dan awareness of this methods remain low. This community service activity aims to improve knowledge, awareness, and skills of healthworkers (both medic and paramedic) and women members of the Polaris group at a family doctor clinic, through BSE adng CBE methods to reduce diagnostic delays, Thereby decreasing the morbidity and mortality rates due to breast cancer. the activity was conducted in the form of interactive counselling, demonstration, and direct guidance to practice using mannequin for BSE and CBE techniques at the family doctor clinic of muhammadiyah university, palembang. An evaluation was conducted using questionnaires to assess risk factors, knowledge, and participant’s attitude. there was improvement in knowledge, with approximatetly 85% of respondent demonstrating good knowledge after counselling, while awareness of high risk factor for breast cancer remained relatively low at 30%. Most participant showed increased awareness to routinely perform BSE and were willing to undergo CBE at healthcare facilities. education on BSE and CBE technique is effective in increasing knowledge, attitudes, and awareness of early detection of breast cancer. This program needs to be conducted regularly in community settings, starting from public health centers and schools, by providing special training and facilitating routine service schedules for CBE